2015
DOI: 10.1016/j.neuroscience.2015.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Qualitatively different effect of repeated stress during adolescence on principal neuron morphology across lateral and basal nuclei of the rat amygdala

Abstract: Repeated stress can elicit symptoms of depression and anxiety. The amygdala is a significant contributor to the expression of emotion and the basolateral amygdala (BLA) is a major target for the effects of stress on emotion. The adolescent time period may be particularly susceptible to the effects of stress on emotion. While repeated stress has been demonstrated to modify the morphology of BLA neurons in adult rats, little is known about its effects on BLA neurons during adolescence. This study tests the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 108 publications
(134 reference statements)
6
14
0
Order By: Relevance
“…In contrast, there was little evidence for increased glutamatergic drive after repeated stress in adolescent rats. In fact, a decrease of mEPSC frequency was observed, consistent with recent findings that repeated stress decreases the number of spines on LAT neurons in adolescent rats (Tsai et al, 2014;Padival et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, there was little evidence for increased glutamatergic drive after repeated stress in adolescent rats. In fact, a decrease of mEPSC frequency was observed, consistent with recent findings that repeated stress decreases the number of spines on LAT neurons in adolescent rats (Tsai et al, 2014;Padival et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The increased excitatory response to glutamate could be caused by increased neuronal membrane excitability (Rosenkranz et al, 2010;Hetzel and Rosenkranz, 2014), increased function of NMDA or AMPA receptors (Adamec et al, 2005;Caudal et al, 2010;Mozhui et al, 2010;Suvrathan et al, 2014), reduced glutamatergic drive of GABAergic networks (Masneuf et al, 2014), or upregulation of glutamatergic receptors (Lei and Tejani-Butt, 2010;Gan et al, 2014). Increased glutamatergic synaptic transmission could be caused by increased glutamatergic inputs, as observed here and in other studies (Mitra et al, 2005;Vyas et al, 2006;Padival et al, 2013Padival et al, , 2015Suvrathan et al, 2014;Tsai et al, 2014). In contrast, there was little evidence for increased glutamatergic drive after repeated stress in adolescent rats.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This may be due to differential effects of stress between LA and BLA neurons. For example, it has been reported that chronic stress has little impact on total dendritic length within LA neurons in adult mice (65–73 days old; similar to the age at which mice received foot‐shock stress in this study; Padival et al, ). Therefore, the increase in sEPSC activity in the absence of a significant increase in total dendritic length is in agreement with published data when taking the region of the amygdala and the age of the mice into account.…”
Section: Discussionsupporting
confidence: 78%
“…Neural activity, neurotransmitter release, and growth factors are also disrupted during social isolation in rats before or after weaning (Cirulli et al, 2003;Chatterjee et al, 2007;Le on-Rodr ıguez and Dueñas, 2013;Toda et al, 2014;Wang et al, 2015), and these alterations associate with glial underdevelopments. The main structures affected are amygdala (Fleming et al, 1994;Sanchez et al, 1995;Lyons et al, 2010;Lukkes et al, 2012;Toda et al, 2014;Padival et al, 2015), the medial prefrontal cortex (Silva-G omez et al, 2003;Braun et al, 2009;Miyazaki et al, 2012;Wall et al, 2012;Tada et al, 2016), hippocampus (Silva-G omez et al, 2003;Bonab et al, 2012;Wang and Gondr e-Lewis, 2013), and the HPA axis (Akbari et al, 2008;Daniels et al, 2009;Vargas et al, 2016).…”
Section: Discussionmentioning
confidence: 99%